Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1161/hypertensionaha.109.133736
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Nitration of PA700 Activates the 26S Proteasome to Induce Endothelial Dysfunction in Mice With Angiotensin II–Induced Hypertension

Abstract: Abstract-The ubiquitin-proteasome system has been implicated in oxidative stress-induced endothelial dysfunction in cardiovascular diseases. However, the mechanism by which oxidative stress alters the ubiquitin-proteasome system is poorly defined. The present study was conducted to determine whether oxidative modifications of PA700, a 26S proteasome regulatory subunit, contributes to angiotensin II (Ang II)-induced endothelial dysfunction. Exposure of human umbilical vein endothelial cells to low concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 52 publications
6
45
0
1
Order By: Relevance
“…4B), consistent with our previous studies [12]. Furthermore, siRNA-mediated PA700/S10B knockdown prevented association of 26S proteasome sub-complexes as expected (Fig.…”
Section: Resultssupporting
confidence: 92%
“…4B), consistent with our previous studies [12]. Furthermore, siRNA-mediated PA700/S10B knockdown prevented association of 26S proteasome sub-complexes as expected (Fig.…”
Section: Resultssupporting
confidence: 92%
“…During CVD, the endothelium losses its homoeostatic potential to inhibit the disease process [38]. We [39], [40], [41] and others [42] have shown that the UPS can contribute to the development of endothelial dysfunction, which is reflected as enhanced 26S proteasome activity, an accelerated degradation of endothelial-protective molecules (such as the guanosine 5-triphosphate cyclohydrolase I or GTPCH I, the rate limiting enzyme essential for the de novo synthesis of an eNOS co-factor [39], [40], [43]), and consequent impaired endothelium-dependent vasorelaxation. Most importantly, we have discovered that such an impairment can be restored by activation of AMPK [43].…”
Section: Introductionmentioning
confidence: 99%
“…17 The 26S proteasome responsible for this degradation has been shown for getting activated by nitration of specific tyrosine residues in the setting of hyperglycemia 17 and experimental hypertension, 18 only leaving the salvage pathway for restoration of BH 4 levels via reduction of dihydrobiopterin (BH 2 ) by dihydrofolate reductase (DHFR). 19 Taking into account that BH 4 plays an essential role for eNOS function, its oxidative depletion or simultaneous inhibition of its de novo synthesis will ultimately lead to eNOS dysfunction/uncoupling, despite the futile counterregulatory upregulation of DHFR expression and activity.…”
Section: See Accompanying Article On Page 2366mentioning
confidence: 99%